Delayed tooth repalantetion after treatment of necrotic periodontal ligament with citric acid - Cardoso, Leandro de Carvalho [UNESP]; Luvizuto, Eloá Rodrigues [UNESP]; Poi, Wilson Roberto [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Truiti, Daniela Naves [UNESP]; Sonoda, Celso Koogi [UNESP]; Andrade, Paulo Barbosa [UNESP] (Editora Cubo, 2012)
Objective: to evaluated the effect of treating root-adhered necrotic periodontal ligament (PDL) with citric acid on the healing process in delayed rat tooth replantation. Material and Methods: Forty Wistar rats, assigned to 4 groups (n=10), had their upper right incisor extracted and kept dry on a workbench. For Group I (control), the teeth were replanted after a 5 min extra-alveolar time. For the other groups, replantation was done after 60 min. In Group II, the root canals were filled with a calcium hydroxide-based paste and the teeth were replanted with no root surface treatment. In Group III, the teeth were immersed in citric acid (pH 1) for 3 min, the canals were filled with calcium hydroxide and the teeth were replanted. In Group IV, instead of the immersion, the roots were scrubbed with gauze soaked in citric acid and the teeth were replanted. The animals were sacrificed 60 days postoperatively. Results: Regarding replacement resorption, there was statistically significant difference (p < 0.05) between the control group and the other three groups. No statistically significant difference (p > 0.05) was found among the groups regarding the areas of inflammatory resorption. There was also a statistically significant difference (p < 0.05) between the control group and Group IV regarding ankylosis. The control group showed the least replacement resorption percent means compared to the other groups (p < 0.05). The root structure was more affected by replacement resorption and ankylosis in Group IV compared to the Groups II and III, but this difference was not significant statistically (p > 0.05). Conclusion: the treatment of root surface-adhered necrotic periodontal ligament with citric acid was not able to prevent the occurrence of ankylosis, root resorption and inflammatory resorption in delayed rat tooth replantation.

Objetivo: avaliar o efeito do ácido cítrico no ligamento periodontal cementário necrótico no processo de reparo do reimplante dentário tardio em rato. Material e Método: Quarenta ratos Wistar após a extração do incisivo superior direito foram divididos em 4 grupos (n=10). No Grupo I (controle), os dentes foram reimplantados após 5 min extralveolar. Nos outros grupos o reimplante foi realizado após 60 min. No Grupo II, os canais foram obturados com pasta hidróxido de cálcio e os dentes foram reimplantados sem tratamento da superfície radicular. No Grupo III, os dentes foram imersos em ácido cítrico (pH1) por 3 min, os canais foram obturados com pasta de hidróxido de cálcio e reimplantados. No Grupo IV, a superfície radicular foi friccionada com gaze embebida em ácido cítrico e os dentes reimplandos. Os aminais sofreram eutanásia 60 dias após o reimplante. Resultados: Quanto à reabsorção por substituição houve diferença estatisticamente controle e do Grupo IV quanto a anquilose. O grupo controle apresentou menor reabsorção por substituição em comparação com os outros grupos (p < 0,05). A estrutura radicular foi mais comprometida pela reabsorção por substituição e anquilose no Grupo IV quando comparado aos grupos tratamento do ligamento periodontal cementário com ácido citrico reimplante dentário tardio em rato.
Reimplante dentário tardio após tratamento do ligamento periodontal necrótico com ácido cítrico
Keywords: Avulsion; Tooth replantation; Rats; Trauma; Periodontal ligament; Root surface treatment; Avulsão; Reimplante dentário; Rato; Trauma; Ligamento periodontal; Tratamento de superfície